Собачье сердце: [сборник] / М. А. Булгаков - Булгаков Михаил Афанасьевич (Эксклюзив, 2018)
Экземпляры: Селтинская районная библиотека (аб) (20190306) / Инвентарный номер: 205946 / Цена: / Авт.знак: Б 90 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6